PENEGAKAN KODE ETIK KEDOKTERAN DI INDONESIA - Deny Haspada (Scientia Regendi, 2020)
All medical actions of doctors against patients must be professionally accounted for. That sense of responsibility is based on the good intentions of a doctor in carrying out his activities with the knowledge of medical ethics. As a public health steward a doctor must be willing to serve his body and soul for the benefit of the wider community. Even so, it is not uncommon to find a number of violations of medical ethics in the news available, or maybe even experience it yourself.